Insecure Attachment Predicts History of Divorce, Marriage, and Current Relationship Status. Issue 5 (4th July 2019) - McNelis, Melissa; Segrin, Chris
ABSTRACT: The goal of this research was to test the predictive ability of attachment styles and dysfunctional relational communication patterns to predict adults' relationship status (i.e., single/partnered and ever-married/ever-divorced). Anxious and avoidant attachment styles and dysfunctional relational communication patterns (i.e., criticism, defensiveness, contempt, stonewalling) were predictors of relationship status in 413 adults who participated in an online survey. The results indicated that anxious and avoidant attachment styles significantly predicted both history of divorce and single versus partnered relationship status. The dysfunctional communication patterns did not explain a great deal of variance in relationship history and status above and beyond insecure attachment, although dysfunctional communication was significantly and consistently associated with insecure attachment. These results indicate that some of the individual characteristics that generate a risk for divorce might also pose a barrier to repartnering after a divorce.